Circe’s magic: from Boethius’ De Consolatione Philosophiae to the Old English and Old High German versions - Carla Riviello (Filologia Germanica)
In the Old English and Old High German versions of De Consolatione Philosophiae, Circe’s character (co- protagonist with Ulysses in Book IV, Metre 3) substantially reflects the description Boethius gave of her. According to Boethius, the sorceress was not particularly powerful as she had no influence over the minds of her victims. Analysing the translation strategies adopted, we can see how, in both cases, despite a declared unfamiliarity with magic, the representation modalities reveal an otherwise obvious familiarity with its procedures. And yet, the different cultural-historical contexts in which the two translations were carried out, and the different demands and purposes under the impulse of which they were promoted and brought to life, define a different approach to the re-writing of the myth. On the one hand, if devaluing the power of magic was a manifest political need at King Alfred’s court, on the other, in the conventual school of Saint Gall, the stigmatisation of magic made way for the educational necessity of translating Boethius’ work in order to explain its complexity with precise and perspicuous lexical choices.